ANALISIS BIAYA ELEMENTAL UNTUK PERENCANAAN BIAYA PROYEK APARTEMEN - Kempa, Meidy; Andi, Andi; Arijanto, Lie (JURNAL DIMENSI UTAMA TEKNIK SIPIL, 2014)
Apartmentâs project cost planning involves a Quantity Surveyor to determine the target cost (budget) for the owner. Target cost must included all elements of the existing building. This study aims to determine the format and price range of each building element in the elemental cost analysis for apartmentâs project cost planning.The data were obtained by looking at historical data of the middle classÂ  apartmentâs projects Bill of Quantity in area of Surabaya, Solo and Semarang with reference to the format NPWC List of Elements, Australia.The results of the data analysis showed that the format of building elements that can be used in elemental cost analysis consists of 11 major elements are Preliminaries, Sub-structure, Super-structure, Finishes, Fittings, Services, Site Works, External Services, Waterproofing, Grills & Iron, and Pool. While the price range of elements in the elemental cost analysis showed that the apartmentâs project which has a basement, the price difference is 20-30% larger than projects that do not have a basement. For the project which has storey height â¥ 3m, the price difference is 3.5-20% larger than projects which has storey height < 3m. For projects which has a basement & storey height â¥ 3m, the price difference is 30% larger than the project which has a basement & storey height <3m.Â Keyword : cost planning, target cost, apartmentâs project, building elements, elemental cost analysis